Application of the ESC and AHA guidelines for admission of syncope patients presenting to the ED. (25th November 2020) - Du Fay De Lavallaz, J; Zimmermann, T; Badertscher, P; Flores, D; Widmer, V; Walter, J; Strebel, I; Lopez-Ayala, P; Wussler, D; Koechlin, L; Di Somma, S; Keller, D; et al.
Abstract: Background: Syncope in the ED is linked with high diagnostic and prognostic uncertainty, leading to an extremely high rate of admissions. These often inappropriate admissions are costly and expose patients to unnecessary testing. The recent ESC and AHA guidelines aim at reducing these admissions by stratifying patients in high- and low-risk groups. Methods: The BASEL IX Syncope study is a large prospective international multicenter study recruiting patients 40 years presenting to the ED with syncope within the last 12 hours in eight countries on three continents. Cardiac syncope was centrally adjudicated by two physicians using all data collected up to 1-y follow-up. We classified patients as requiring admission or being judged safe for discharge according to the ESC and AHA guidelines criteria and compared these with the physician's decision regarding hospitalization. We assessed the consequence of these decisions on 30-day serious cardiac events and mortality. We validated our findings in a large American cohort recruiting syncope patients >60 years in 11 EDs. Results: 1977 patients were eligible for this analysis. 215 (10.8%) experienced 30-day Major Adverse Cardiovascular Events (MACE). The ESC and AHA guidelines would have admitted a largely different number of patients (75.9% vs 29.6%) and provided different safety regarding adverse events and death at 30 days (Figure). The validation in the US cohort provided similar results, however US ED physicians decided to admit more patients (84%) as compared with the international derivation cohort (46.6%). Conclusion: The AHA and ESC syncope guidelines recommend admission based on very different criteria and for a largely different number of patients. While the most recent ESC guidelines were written with the aim to limit the number of patients admitted, they still classify a large majority of an ED syncope cohort as high risk and warranting admission. The large discrepancy between the two guidelines is based on the criteria used for the classification: While the ESC guidelines consider risk factors, previous cardiac history, physical examination and ECG criteria, the AHA guidelines focus on serious conditions previously known or diagnosed in the ED. Figure: Percentage of the overall cohort admitted (green) or discharged (red) according to the AHA and ESC guidelines and to the decision of the physician in the BASEL-IX cohort. Patients experiencing a cardiac syncope, a 30-day MACE or death are represented for both the discharged and admitted groups. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): University hospital Basel